Integrity - Villoria, Manuel (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
This works states the moral support of the idea of integrity and projects it on the functionality and the organization of the public institutions. Moreover, it analyzes its implications for the good governance and the characteristics of the integrity frames.
Keywords: Virtue; good governance; professional ethics; integrity systems; integrity frameworks